The Canadian Ocean Mapping Research and Education Network (COMREN) - Church, Ian; Daniel, Sylvie; Mullan, Sean; Purcell, Michael; Laflamme, Jean; Knudby, Anders; Bisnath, Sunil; Galway, Sean; Hains, Denis (The International Hydrographic Review, 2020)
In Canada, ocean, river, lake and coastal mapping knowledge, capacity building and know-how are strengthened through a network of members from academic institutions and one nonprofit organization. This note highlights the Canadian Ocean Mapping Research and Education Network (COMREN), its purpose and its membership.